Perhitungan Struktur Pada Box Culvert STA. 0+050 Proyek Bendungan Bener Paket 3, Purworejo - Ryandika, Ahmad; Romadhon, Eri Setia (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2025)
In order to fulfill the requirement for andesite rock in the construction of the dam body, it is necessary to provide an access road to the quarry site. Accordingly, a box culvert structure is designed to facilitate this access road as it traverses a tributary, thereby ensuring that the construction activities do not disrupt the function of the existing river flow. This study aims to calculate the structural strength of a box culvert for the Bener Dam Project using a quantitative approach. The research began with initial stages including data collection, determination of the planned loads acting on the structure, and the development of a preliminary design for the structural dimensions. The collected data were then analyzed using SAP2000 software, allowing for the structural behavior to be evaluated in detail. The results of the analysis were used to determine the required reinforcement so that the final conclusion could be made regarding the safety and feasibility of the designed structure. The outcome of this research is expected to serve as a reference for ensuring that the planned box culvert structure can adequately support the intended loads and maintain safety standards during the construction of the access road for the quarry at the Bener Dam Project. The calculation results show that the cross-sectional dimensions of the box culvert are 4.5 meters by 4.5 meters. For flexural reinforcement, the ultimate moment (Mu) is less than the nominal moment capacity (Mn), and for shear reinforcement, the ultimate shear force (Vu) is less than the nominal shear capacity (Vn), indicating that the structural design is safe to withstand the applied loads. The maximum deflection for the floor slab is 1.046 mm and for the wall slab is 8.626 mm, both of which are below the allowable limit of L/250. Therefore, it can be concluded that the designed structure is safe and sufficiently strong to carry the intended loads.